Coaches' Immigration to the United Kingdom: What do Foreign and Native Coaches think about migration - Alessandra Sain; Mario Borges; Rita De Oliveira (Universidad Pablo de Olavide, 2022)
Coaches' migration has received limited attention. It is important to explore their migration experiences and how native coaches perceive coaches' migration because they might have different views on this topic. The current research aims to investigate a) the perceptions of migrant coaches regarding their experiences in a host country and b) the perceptions of native coaches regarding coaches' migration to the UK. A qualitative thematic analysis was adopted to analyse the data and MAXQDA 11 software was used to facilitate this process. In total, 15 participants residing in the UK were invited to participate through convenience sampling. An online open-ended survey was completed by ten immigrant coaches (six females, four males) with ages ranging from 19 to 44 years (mean = 30.7; SD = 9.04), and interviews were conducted with five British native coaches (four males and one female) with ages ranging from 20 to 40 years (mean = 30.5; SD = 9.15). We found that coaches' transnational recruitment was mainly influenced by social networks. Immigrant coaches were motivated to migrate to the UK to work full-time in their sport. They reported some language and communication challenges in their adaptation and suggested training for migration purposes would have been useful. UK-native coaches defined coaches' immigration as positive for the UK sports development and the exchange of knowledge and skills in the sport. However, they also identified barriers imposed on immigrant coaches such as other coaches' negative views about immigration and protectionist measures from the UK sports federations.